Gestión del riesgo climático mediante derivados. Aplicación al sector de líneas aéreas en México y España - López Domínguez, Ignacio (2022)
The purpose of this research is to analyze the use of weather derivatives as a hedge of this source of risk, both in the Spanish and the Mexican market, in order to minimize the negative impact that the economic activities of the companies in each market have on the behavior of the weather. In order to this, first we identify the weather risk suffered by Mexican and Spanish companies of the airline industry, analyze the management thereof through the use of weather derivatives, and conclude with a comparative study of the improvement of the management of these companies after the use of said products. The most relevant conclusion is that the implementation works better in the Mexican sector since it is more sensitive to weather. In the case of Spain, there is an improvement in the quality of dealing with weather risks; however, it is necessary to maintain an administration of weather risk in order to minimize the uncertainty caused by climate change.